2013
DOI: 10.1007/s13538-013-0116-3
|View full text |Cite
|
Sign up to set email alerts
|

Description of Even–Even 114–134Xe Isotopes in the Transitional Region of IBM

Abstract: Properties of 114 134 Xe  isotopes are studied in the (5) (6) U SO  transitional region of Interacting Boson Model (IBM-1). The energy levels and ( 2) BE transition rates are calculated via the affine (1,1) SU Lie Algebra. The agreement with the most recent experimental is acceptable. The evaluated Hamiltonian control parameters suggest a spherical to   soft shape transition and propose the 130 Xe nucleus as the best candidate for the (5) E symmetry.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…Although the results of this approach are somewhat different from those of the IBM, but as have presented in Refs. [61][62][63][64], a clear correspondence with the description of the geometrical model is obvious for this transitional region.…”
Section: Theoretical Description Of Transitional Region and Shape Coe...supporting
confidence: 57%
See 2 more Smart Citations
“…Although the results of this approach are somewhat different from those of the IBM, but as have presented in Refs. [61][62][63][64], a clear correspondence with the description of the geometrical model is obvious for this transitional region.…”
Section: Theoretical Description Of Transitional Region and Shape Coe...supporting
confidence: 57%
“…g and  are real parameters where 2 ( (3)) C SO and 2 ( (5) ... , Then, we have used "Find root" in the Maple17 to get all ' j y s. We carry out this procedure with different values of c and  to provide energy spectra (after inserting  and  ) with minimum variation as compared to the experimental counterparts; Refs. [61][62][63][64] extensively, in the Tellurium isotopes, the normal vibrational states are mixed with deformed intruder states and therefore one may use the IBM-2 calculation to explore three phonons or 2p-4h states with more accuracy in comparison with IBM-1.…”
Section: Representations Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that 134 Xe can be described as vibrational [3][4][5]. The N = 80 isotone 136 Ba has been studied with the (n, n ′ γ) reaction in our laboratory [26], and the transition strengths of the two-phonon states were found to be consistent with the vibrational picture and candidates were proposed for three-phonon excitations.…”
Section: Discussionmentioning
confidence: 78%
“…Recent computational studies within the interacting boson model [3][4][5] describe 134 Xe as "vibrational"; however, the detailed experimental data supporting this description are not available. For example, according to the most recent data compilation [6], the spin-parity of the second excited state is not firmly established and a putative 0 + excitation, the third excited state, has been reported in inelastic neutron scattering (INS) but has not been observed with other reactions.…”
Section: Introductionmentioning
confidence: 99%